Non‐lethal loop‐mediated isothermal amplification assay as a point‐of‐care diagnostics tool for Neoparamoeba perurans, the causative agent of amoebic gill disease. Issue 7 (4th May 2020) - Cano, Irene; McCullough, Robin; Mulhearn, Brian; Gunning, Susie; Waine, Ava; Joiner, Claire; Paley, Richard
Abstract: Neoparamoeba perurans is the causative agent of amoebic gill disease (AGD). Two loop‐mediated isothermal amplification (LAMP) assays targeting the parasite 18S rRNA and the Atlantic salmon EF1α, used as internal control, were designed. The N. perurans LAMP assay did not amplify close relatives N. pemaquidensis and N. branchiphila, or the host DNA. This assay detected 10 6 copies of the parasite 18S rRNA gene under 13 min and 10 3 copies under 35 min. Five "fast‐and‐dirty" DNA extraction methods were compared with a reference method and further validated by TaqMan™ qPCR. Of those, the QuickExtract buffer was selected for field tests. Seventy‐one non‐lethal gill swabs were analysed from AGD‐clinically infected Atlantic salmon. The pathogen was detected under 23 min in fish of gill score >2 and under 39 min for lower gill scores. About 1.6% of the tests were invalid (no amplification of the internal control). 100% of positives were obtained from swabs taken from fish showing gill score ˃3, but only ~50% of positives for lower gill scores. The present LAMP assay could be implemented as a point‐of‐care test for the on‐site identification of N. perurans ; however, further work is required to improve its performance for lower scores .